Artificial intelligence in soil science: Where do we go now? - Jose Pablo Castro; Caley K. Gasch; Paulo Flores (Agricultural & Environmental Letters)
Abstract Recognizing the fast advancement of artificial intelligence (AI) in soil science, the main objective of this commentary paper is to discuss how this technology is being incorporated into the discipline, focusing on the most common algorithms and their applications. Employing a discursive and reflective methodology, the article draws insights from the authors' expertise and opinions. The paper explores some ethical considerations and the potential impact of AI on the job market and calls for a balanced approach that maximizes the benefits of this technology while vigilantly mitigating its negative implications to ensure the integrity and inclusivity of the profession. Core Ideas Artificial intelligence (AI) is changing soil science with advanced analytic and predictive modeling tools. Ethical AI in soil science should focus on data integrity, privacy, and transparent research. AI is reshaping the soil science job market, emphasizing the need for adaptability, and continuous learning. Collaboration between technology and soil experts can lead to groundbreaking research and academic solutions. AI, as a complementary tool, can enhance soil scientists' expertise, creativity, and problem‐solving abilities.